Chromatin accessibility landscape of pediatric T‐lymphoblastic leukemia and human T‐cell precursors - Büşra Erarslan‐Uysal; Joachim B Kunz; Tobias Rausch; Paulina Richter‐Pechańska; Ianthe AEM van Belzen; Viktoras Frismantas; Beat Bornhauser; Diana Ordoñez‐Rueada; Malte Paulsen; Vladimir Benes; Martin Stanulla; Martin Schrappe; et al. (EMBO Molecular Medicine, 2020)
Abstract We aimed at identifying the developmental stage at which leukemic cells of pediatric T‐ALLs are arrested and at defining leukemogenic mechanisms based on ATAC‐Seq. Chromatin accessibility maps of seven developmental stages of human healthy T cells revealed progressive chromatin condensation during T‐cell maturation. Developmental stages were distinguished by 2,823 signature chromatin regions with 95% accuracy. Open chromatin surrounding SAE1 was identified to best distinguish thymic developmental stages suggesting a potential role of SUMOylation in T‐cell development. Deconvolution using signature regions revealed that T‐ALLs, including those with mature immunophenotypes, resemble the most immature populations, which was confirmed by TF‐binding motif profiles. We integrated ATAC‐Seq and RNA‐Seq and found DAB1, a gene not related to leukemia previously, to be overexpressed, abnormally spliced and hyper‐accessible in T‐ALLs. DAB1‐negative patients formed a distinct subgroup with particularly immature chromatin profiles and hyper‐accessible binding sites for SPI1 (PU.1), a TF crucial for normal T‐cell maturation. In conclusion, our analyses of chromatin accessibility and TF‐binding motifs showed that pediatric T‐ALL cells are most similar to immature thymic precursors, indicating an early developmental arrest.